Development of capability lists for neonatal critical care at three levels in China: a modified Delphi study - Lei Li; Yanping Zhang; Ting Li; Qian Zhang; Xing Li; Shan Zhang; Qiuping Li; Lu Zhuang; Zhichun Feng; Pengpeng Li; Xiangyong Kong (BMJ Publishing Group, 2024)
Background The standardised management of neonatal critical care centres can help improve health outcomes of vulnerable newborns. Guidance is required to update evidence related to construction and management of neonatal critical care centres in China.Objective To establish expert consensus on the essential capability lists for neonatal critical care at three levels in China.Design and setting According to China's administrative divisions, the Chinese guidelines stratifies neonatal critical care into three levels: county level (basic and special care), city level (intensive care) and province level (comprehensive care including neonatal surgery and more subspecialty interventions). A modified Delphi study was conducted. A group of 20 neonatologists from the Chinese Association of Neonatologists rated the importance of capability items on a 5-point Likert scale.Results At county level, the list consisted of 29 items related to basic and special care, and 3 items were unanimously rated very important by all experts: neonatal resuscitation, endotracheal intubation and continuous positive airway pressure ≥72 hours. At city level, group consensus defined 38 items as essential. Besides the essential items of county level, more items for intensive care were included in city level. At province level, 64 items reached consensus, including neonatal surgery and more advanced subspecialty interventions. The Kendall's W values showed good agreement among experts in both rounds, and an increase from round 1 to round 2.Conclusions We developed the capability lists for neonatal critical care at three levels in China. Neonatal resuscitation should be provided by all levels. Interventions for preterm newborns are stratified according to gestational age and birth weight. Congenital abnormalities requiring surgical services need to be managed in high-level centres.